Implementation of the digital government policy during the pandemic, in the Secretary of Education of the District, in the PQRS process in the year 2020 (2022)
The present investigation deals with the implementation of the digital government policy in Colombia, its different elements are identified and what has been its importance since the management of the national government, the relationship with other policies where the use of communication technologies is encouraged. and information, in order to locate its implementation in the Secretary of Education entity of the District, especially for the period 2020-2021, years during which the COVID-19 pandemic was experienced. It will be identified through which plans, policies and processes the policy is implemented within the SED, taking into account that this policy is part of the MIPG as a tool and is identified within the entity's support processes, within the main policies and plans are identified the information security management subsystem policy, the Strategic Plan for Information and Communication Technologies 2020-2024 and the security and privacy risk treatment plan where the elements defined for the digital government policy are managed. Statistics are also presented that allow inferring what were the main changes that the SED's PQRS process presented and how the SED's implementation of the digital government policy affected them.